2016
DOI: 10.5336/dentalsci.2016-52123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Treatment Effects of Two Intrusive Mechanics: Connecticut Intrusion Arch and Mini-Implant

Abstract: A AB BS S T TR RA AC CT T O Ob bj je ec ct ti iv ve e: : The aim of this study was to compare the treatment efficiencies and root resorption amounts of two different incisor intrusion mechanics. M Ma at te er ri ia al l a an nd d M Me et th ho od ds s: : Thirty-two patients with deep bite and elongated maxillary incisors were randomly allocated two treatment groups: Connecticut intrusion arch group (CG) or Mini-implant group (MG). In both groups approximately 60 g of force applied between central and lateral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The full text of the remaining 30 studies (21 studies by database search and 9 studies after manual search) were retrieved and analyzed, 5 of them because only the amount of vertical control of teeth during retraction was assessed and 10 of them were excluded because they did not have a mini-screw group. A total of 15 articles were included in our study for systematic review [ 15 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], and after data extraction, meta-analyses were performed on 14 studies, and for one study [ 42 ], only a systematic review was performed due to differences in outcomes and retainers under review with the rest of the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full text of the remaining 30 studies (21 studies by database search and 9 studies after manual search) were retrieved and analyzed, 5 of them because only the amount of vertical control of teeth during retraction was assessed and 10 of them were excluded because they did not have a mini-screw group. A total of 15 articles were included in our study for systematic review [ 15 , 29 , 30 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], and after data extraction, meta-analyses were performed on 14 studies, and for one study [ 42 ], only a systematic review was performed due to differences in outcomes and retainers under review with the rest of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 and Figure 4 show a summary of the risk of bias in the included studies. For randomized clinical trials, four studies had an unknown risk of bias while the two studies for Gurlen et al and Ma et al [ 37 , 39 ] had a high risk of bias. For the non-randomized studies, all of them were judged to have a moderate risk of bias mostly because of bias due to confounding factors, bias in selection of participants into the study, and bias in selection of the reported results.…”
Section: Resultsmentioning
confidence: 99%